Teacher Strategies in Overcoming Students' Anxiety During Tests - Lera Atmayanti; Dina Elviana; Muhammad Iksan (CV. Abhinaya Indo Group, 2025)
Around 45% of students in Indonesia experience anxiety related to exams (Kemdikbud, 2022), which is manifested through physical, emotional and cognitive symptoms which can cause a decrease in academic achievement by as much as 15% (Zeidner, 2014). This literature study analyzes teacher strategies based on humanistic theory (Rogers), self-efficacy (Bandura), and CBT (Beck) to overcome these problems. Findings indicate that three effective approaches have been identified: (1) creating a supportive learning atmosphere characterized by consistent encouragement, (2) increasing self-confidence through affirmative feedback and assessment preparation, and (3) using cognitive behavioral methods such as changing negative thoughts and applying relaxation techniques. Combining these tactics has shown success in reducing anxiety by increasing self-regulation and reducing feelings of danger. Possible strategies to consider might include: (a) avoiding competitive grading systems, (b) adopting alternative grading methods (such as portfolios or projects), and (c) working with school counselors. This research emphasizes the importance of a balanced evaluation approach between academic achievement and students' psychological well-being.